Venous thromboembolism prophylaxis in Asian patients with severe COVID-19: A prospective cohort study - Nithita Nanthatanti; Pichika Chantrathammachart; Kanin Thammavaranucupt; Kulapong Jayanama; Nuttee Supatrawiporn; Sithakom Phusanti; Somnuek Sungkanuparph; Sirawat Srichatrapimuk; Suppachok Kirdlarp; Supawadee Suppagungsuk; Thananya Wongsinin; Dhanesh Pitidhammabhorn; et al. (Thrombosis Update, 2024)
The severe coronavirus disease 2019 (COVID-19) triggers various coagulation cascades, culminating in the manifestation of venous thromboembolism (VTE). The efficacy of anticoagulant prophylaxis in averting VTE occurrence in severe COVID-19 cases in Thailand remains uncertain. We aimed to determine the prevalence of symptomatic VTE in patients with severe COVID-19 who received a standard dose of anticoagulants and to evaluate the risk factors. Our prospective cohort study included patients with severe COVID-19 who received anticoagulant prophylaxis. VTE, bleeding events and mortality were monitored until 60 days after VTE prophylaxis initiation. Of the 250 study patients, pulmonary embolism was observed in 7.2% of patients. In a multivariate Cox regression model, endotracheal intubation [hazard ratio (HR) = 13.75; 95% confidence interval (CI) = 2.87–65.82; p = 0.001] and high D-dimer levels [HR = 1.052; 95% CI = 1.023–1.081; p < 0.001) were significantly associated with higher VTE risk within 60 days of VTE prophylaxis. Bleeding and major hemorrhage occurred in 35 (14%) and eight (3.2%) patients, respectively. These findings indicated that a standard dose of anticoagulant may not be sufficient for preventing thrombosis in patients who require intensive care. Further research on the appropriate dose is necessary.